Towards a Unified Vertical Datum in Arab Region - Saad, Abdallah A.; Elsayed, Mona S.; Abdelfatah, Shimaa F. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
In Arab region, there are several Local Vertical Datums (LVD). Most of these datums are based on averaging sea level measurements of a single Tide Gauge (TG) or from multiple TGs. One of the main reasons which negatively affecting the huge regional projects between Arab countries as transportation lines, Petroleum Pipelines, electricity, and other projects which require heights, is the difference in SST at tide gauge sites and differences in measuring techniques. Therefore the Precise geoid determination is considered an important step in eliminating these differences as it represents the base for determination the regional geoid model. This study focuses on presenting two proposals for unification the vertical datum in Arab region and the proposed implementation strategy. Review of available data from previous studies. Provide the best techniques to update, tie, and unify the data in all Arab countries, commensurate with the modern technological development.